STAT6 Immunohistochemistry. - Mayer, Chen; Dahan, Osher; Levartovsky, Asaf; Barshack, Iris; Goldman, Adam; Schvimer, Michael (Archives of Pathology & Laboratory Medicine, 2026)
Context.--Eosinophilic esophagitis (EoE) is a chronic, immune-mediated condition with overlapping histologic features with gastroesophageal reflux disease and other esophagitis subtypes. Current diagnostic criteria based on eosinophil density and basal zone hyperplasia lack specificity, necessitating more reliable tissue biomarkers. Objective.--To evaluate the diagnostic utility of signal transducer and activator of transcription 6 (STAT6) immu-nohistochemistry (IHC) in distinguishing EoE from histologic mimics in esophageal biopsies. Design.--STAT6 IHC was performed on 208 esophageal biopsy specimens, including cases of EoE, treated EoE, reflux esophagitis, other esophagitis, and normal mucosa. A blinded gastrointestinal pathologist scored basal epithelial nuclear staining. Diagnostic performance was assessed using predefined and optimized thresholds. Correlations with eosino-phil density and basal zone hyperplasia were analyzed using Spearman correlation and multivariable linear regression. Results.--Among 151 well-characterized cases, a 50% nuclear staining threshold yielded 95.6% sensitivity and 97.2% specificity for EoE. An optimized 32.5% threshold achieved 100% sensitivity and 95.3% specificity. STAT6 expression strongly correlated with eosinophil density (p = 0.80) and basal zone hyperplasia (p = 0.69), but was not entirely explained by either, indicating STAT6 reflects distinct T helper type 2-mediated epithelial activity. Residual staining was observed in some treated EoE cases despite histologic remission. Conclusions.--STAT6 IHC is a robust, specific bio-marker for EoE that offers high diagnostic accuracy and reflects underlying T helper type 2-driven epithelial signaling. Its application may improve diagnostic precision and support future efforts in disease monitoring and therapeutic response assessment.